Can probiotics play a role in Helicobacter pylori (H. Pylori) eradication? - Sameh Mohamed Fakhry; Mohamed Abdel-Hameed Kandyl; Adel Ferig Hashish; Wafaa Kandeel; Ahmed Mostafa El-Shenawy; Hoda Samir El-Sayed; Mohamed Kamal Dewidar; Sameh Mohamed Badr; Nayra Shaker Mehanna (Egyptian Liver Journal, 2023)
Abstract Background H. Pylori is one of the commonest infectious diseases worldwide. In recent years, PPI-based triple therapy has been described to be losing its efficacy against H. pylori due to high rates of antibiotic resistance, antibiotics-associated side effects, and low compliance. Probiotics are suggested to improve the H. pylori eradication rate when added to H pylori therapy. Probiotics have anti-inflammatory and anti-oxidative mechanisms that may improve bowel microecology and interact with the microbial flora of the gastrointestinal tract to produce a beneficial effect in H Pylori eradication. Probiotics may be also responsible for the reduction of the adverse effects related to H. pylori therapy that may result in treatment failure. Aim of the work In our study, we assessed the role of probiotics in improving the H. Pylori eradication rate and reducing side effects after antibiotic-based therapy. Patients and method One hundred fifty-nine patients positive for H. pylori stool antigen and had never received previously H. pylori eradication therapy, were included in the study, 59 patients received triple therapy alone (Standard group) and 100 patients received triple therapy and probiotics (study group). One hundred fifty patients completed the treatment. Quantification of Lactobacilli and Bifidobacteria concentration in stool was done by PCR before and after therapy. Eradication of H. pylori was assessed in each group by H. pylori stool antigen after 4 weeks of finishing therapy. Results H Pylori eradication rate was higher in patients who received probiotics with standard therapy compared to those who received standard therapy alone. The improvement in the eradication rate was statistically significant when probiotics were received after standard therapy (81.04% versus 71.19%, P-Value 0.021). Short-term diarrhea after antibiotics therapy was significantly lower in patients who received probiotics especially when given before antibiotic therapy (7.50% versus 25.50%, P-value 0.0001). Probiotics may play a role to restore gut dysbiosis as evidenced by stool PCR for Lactobacilli and Bifidobacteria before and after therapy. Conclusion Probiotics have a beneficial role to improve the eradication rate of H. pylori, particularly when given after standard therapy. Adding probiotics was associated as well with less diarrhea as a side effect of antibiotic therapy. Trial registration The trial has been registered on the Pan African Clinical Trial Register website, No of registration, PACTR202304859303467. Registered 24 April 2023 - Retrospectively registered, https://pactr.samrc.ac.za/TrialDisplay.aspx?TrialID=25434 .